(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the elections to the State Duma of Russia in Turkestan, the election of representatives from the region, the creation and activities of the Muslim faction, the commission elected to the Duma and the participation of representatives of Turkestan in it, the commissions created under the Muslim faction and its activities, the passivity of participation of representatives of Turkestan in the Duma and its causes